Evaluation of systolic murmurs by Doppler ultrasonography. Issue 4 (October 1983) - Hoffmann, A; Burckhardt, D
Abstract : Non-invasive continuous and pulsed wave Doppler ultrasonography was performed in 102 consecutive patients with clinically ill defined systolic murmurs to differentiate between flow murmurs, mitral regurgitation, aortic stenosis, and ventricular septal defect, as well as to assess the severity of aortic stenosis. Diagnoses with the Doppler method were based on velocity, direction, and duration of flow signals and were subsequently verified by cardiac catheterisation in all patients. Multiple evaluations were made in 31 patients. Sensitivity and specificity were 0.87 and 0.77 in mitral regurgitation, 0.9 and 1.0 in aortic stenosis, and 1.0 and 1.0 in ventricular septal defect. In 67 patients the estimation of severity of aortic stenosis using the Doppler technique to calculate aortic pressure gradients from maximum flow velocity was significantly correlated with that determined at catheterisation. It is concluded that Doppler ultrasonography is a highly useful technique for the non-invasive evaluation of clinically ill defined systolic murmurs.